In vitro characterization of chicken gut bacterial isolates for probiotic potentials - Anita Mandal; Rabindra K. Mandal; Yichao Yang; Bhuwan Khatri; Byung-Whi Kong; Young Min Kwon (Poultry Science, 2021)
Probiotics often play an important role in improving gut health in chickens through multiple mechanisms, including enhancement of tight junctions, nutrient acquisition, niche colonization, or coaggregation with enteric pathogens. The objective of this study was to characterize lactic acid bacteria (LAB) isolated from the gut of healthy broiler chickens for a number of phenotypes that might be indicative of good probiotic potentials. A total 40 bacterial isolates were isolated from 3-week-old chickens using Man, Rogosa and Sharpe (MRS) agar plates. The bacterial isolates were evaluated in vitro for motility, autoaggregation, pathogen inhibition, pH of overnight culture, growth on different agar plates, and their impact on gut integrity. Selected isolates were genotyped by sequencing the 16S-23S rRNA gene intergenic region. Based on the phenotype and genotype, we identified 20 potential probiotic (PP) isolates that belong to LAB. Multivariate analysis showed that PP isolates were positively correlated with parameters such as growth on MRS agar plate (pH 5.5), pathogen inhibition, and autoaggregation. However, growth on MacConkey agar plates, supernatant pH, motility, and transepithelial electrical resistance were negatively correlated with the PP isolates. Furthermore, in vivo study needs to be performed for evaluation of the utility of these probiotic candidates in poultry production.